A visual on‐site method for African swine fever virus detection in raw pig tissues. Issue 6 (9th August 2020) - Zhao, Xiaoli; Wang, Xiudan; Wang, Xuejiao; Liu, Sen; Jing, Hao; Wang, HaiXia; Shi, Chao; Ma, Cuiping
Abstract: The spread of African swine fever virus (ASFV) leads to high mortality in domestic pigs, and has caused huge losses in the global pork industry. Therefore, the rapid detection of ASFV is essential for the prevention and control of the epidemic. Herein, a denaturation bubble‐mediated strand exchange amplification (SEA) with colorimetric detection strategy for the rapid detection of ASFV was established and the results were visible with the naked eyes. The entire detection process based on isothermal amplification was performed on a portable metal bath only. And the whole process including rapid extraction and visual detection was finished within 50 min. The limit of detection of this method reached to 10 4 copies/μl of plasmid containing p72 gene. And the ASFV was successfully detected in eight different tissue and seven types of pig feed which revealed a strong anti‐interference ability in the presence of complex matrix. Through comparing 94 field positive and negative ASFV samples, excellent performance of SEA assay with 92.86% sensitivity and 100% specificity relative to PCR was observed. The developed method could be used for on‐site detection of ASFV with simplicity, rapidity, and visuality, especially suitable for pork industry food safety and ASFV control in resource‐limited areas. Abstract : We have developed a visual on‐site detection of African swine fever by the denaturation bubble‐mediated strand exchange amplification with colorimetric detection strategy. Combined with rapid extraction, the entire detection process takes only 50 min and only requires a portable metal bath. African swine fever virus was successfully detected in eight different tissues and seven types of pig feed by our method, so our method showed strong anti‐interference ability in complex sample matrix.